2008
DOI: 10.3354/cr00732
|View full text |Cite
|
Sign up to set email alerts
|

Regional climate model simulations of North Atlantic cyclones: frequency and intensity changes

Abstract: Frequency and intensity of cyclones over the North Atlantic are investigated using 2 data sets from simulations with the Rossby Centre regional climate model RCA3. The model domain comprises large parts of the North Atlantic and the adjacent continents. RCA3 is driven by ECHAM5-OM1 general circulation model data for May to December from 1985 to 2000 and May to December from 2085 to 2100 assuming the SRES-A2 emission scenario. We apply an objective algorithm to identify and track tropical and extratropical cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Results of the study of [50], which scored ES = 9, showed an increase in cyclone activity in a large number of projections made in their study. Only one study did not identify a change in wind intensity [47].…”
Section: North Atlantic South Of 60˝nmentioning
confidence: 99%
See 3 more Smart Citations
“…Results of the study of [50], which scored ES = 9, showed an increase in cyclone activity in a large number of projections made in their study. Only one study did not identify a change in wind intensity [47].…”
Section: North Atlantic South Of 60˝nmentioning
confidence: 99%
“…The reported tendency (T) in the long-term evolution of the reported variables was assessed and quantified using the categorical interpretation key (i) T = -1 for a decreasing tendency; (ii) T = 0 for no tendency; and (iii) T = +1 for an increasing tendency. Interestingly enough, in total, only four [45][46][47][48] out of the 58 evaluated studies reported no tendency in any one of the assessed categories of future storminess.…”
Section: Study Evaluation and Ratingmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies with the Canadian Regional Climate model (CRCM) show that it has skill in downscaling large‐scale information to regional scales and in successfully reproducing the means and variations of a number of fields, such as SLP and precipitation [ Denis et al , 2002]. In addition, RCMs have been successfully implemented to investigate possible changes in the future cyclone climatology [ Muskulus and Jacob , 2005; Lionello and Giorgi , 2007; Semmler et al , 2008]. Simulations with the Rossby Center regional climate model RCA2 suggest an 18% decrease in the extratropical cyclone count for the North Atlantic under the SRES‐A2 scenario [ Semmler et al , 2008].…”
Section: Introductionmentioning
confidence: 99%